Measurement of reactive oxygen species by chemiluminescence in diet-induced atherosclerosis: protective roles of vitamin E and probucol on different radical species - YALÇIN, AHMET SUHA; HAKLAR, GONCAGÜL; KARTAL ÖZER, NESRİN; ŞİRİKÇİ, ÖNDER (SPRINGER, 1998)
We have investigated the effects of a high-cholesterol diet on the production of different reactive oxygen species in rabbit aortic rings and evaluated the protective effects of vitamin E and probucol in preventing peroxidative changes. Twenty-five male albino rabbits were divided into five groups. Control rabbits were fed a vitamin E-poor rabbit chow. Rabbits in the second group were given a vitamin E-poor diet supplemented with 2% cholesterol. Other groups received either 50 mg/kg vitamin E, 1% probucol, or both, in addition to 2% cholesterol for 4 weeks. Reactive oxygen species formation in aortic rings was measured by enhanced chemiluminescence using luminol and lucigenin. (The results were given as cpm/mg wet weight.) Further differentiation of radical species involved in luminol-enhanced chemiluminescence was performed using sodium azide and L-nitroarginine, a selective inhibitor of nitric oxide production. Our results indicated that cholesterol feeding increased lucigenin and luminol chemiluminescence, where the contribution of free radicals inhibited by sodium azide (radicals originating from endothelial cells or from phagocytes) were 53% and peroxynitrite 24%. Both vitamin E and probucol were effective as scavengers of free radicals, but the effect of vitamin E was more pronounced. In conclusion, the present study demonstrated excessive generation of reactive oxygen species within the atherosclerotic vessel. Peroxidative changes could be prevented by vitamin E and probucol treatment, but vitamin E seemed to be more efficient.
Keywords: atherosclerosis; superoxide radical; chemiluminescence; vitamin E; probucol; LOW-DENSITY-LIPOPROTEIN; SUPEROXIDE ANION PRODUCTION; RECEPTOR-DEFICIENT RABBITS; LIPID PEROXIDES; RELAXING FACTOR; NITRIC-OXIDE; OXIDIZED LDL; ANTIOXIDANTS; ENDOTHELIUM; RELEASE